THE PERSPECTIVE OF THE STUDENTS OF UNIVERSITAS KRISTEN INDONESIA REGARDING ONLINE LEARNING METHOD DURING THE COVID-19 PANDEMIC - Gunawan Tambunsaribu; Yules Orlando Sianipar; Teguh Prasetyo (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
The COVID-19 pandemic forced educational institutions worldwide to rapidly transition from traditional face-to-face learning to online learning systems. This qualitative study aims to explore the perspectives of English Literature students at Universitas Kristen Indonesia regarding their experiences with online learning methods during the pandemic. Data were collected through interviews and field notes from 23 active students who experienced full online learning from 2020 until 2023. Using purposive sampling, the research focused on student responses to four main questions addressing their likes, dislikes, encountered barriers, and suggestions for improving online learning methods. The findings revealed that while students appreciated the flexibility, varied learning media, and opportunities for independent study, they also encountered numerous challenges, including internet connection problems, device limitations, excessive workloads, concentration difficulties, and monotonous teaching methods. The research highlights the importance of integrating interactive, flexible, and creative teaching approaches, improving digital literacy for both lecturers and students, and fostering positive lecturer-student interactions. This study contributes uniquely by providing in-depth qualitative insights from students within a specific program and institutional setting in Indonesia. It offers valuable recommendations for teaching practitioners and educational institutions to enhance the effectiveness and engagement of online learning systems, especially in similar crises or blended learning environments in the future.